2021
DOI: 10.3389/fpsyt.2021.710435
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness in Depression and Obstructive Sleep Apnea: More Than Just an Overlapping Symptom

Abstract: Excessive daytime sleepiness (EDS) is a significant public health concern, with obstructive sleep apnea (OSA) being a common cause, and a particular relationship exists with the severity of depression. A literature search on OSA, depression, and EDS was performed in PubMed. The chosen evidence was limited to human studies. Available evidence was systematically reviewed to ascertain the association of EDS with depression and OSA according to the general population and some specific population subgroups. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
13
0
2
Order By: Relevance
“…OSA cases include the repeated occurrence of hypoxemia, hypercapnia, and sleep structure disorders at night, along with well-accepted related damages, such as cardiovascular, cerebrovascular, and metabolic dysfunctions ( 1 ). Understanding the potential pathological contributions of OSA to cancers, depression, and asthma can also update our knowledge of its biological effects ( 2 , 3 ). In addition, a previous cross-sectional study involving 3,303 subjects showed that OSA was an independent risk factor for dry eye disease (DED) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…OSA cases include the repeated occurrence of hypoxemia, hypercapnia, and sleep structure disorders at night, along with well-accepted related damages, such as cardiovascular, cerebrovascular, and metabolic dysfunctions ( 1 ). Understanding the potential pathological contributions of OSA to cancers, depression, and asthma can also update our knowledge of its biological effects ( 2 , 3 ). In addition, a previous cross-sectional study involving 3,303 subjects showed that OSA was an independent risk factor for dry eye disease (DED) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the known protective effects of smoking for PD [24] and increased PD risk due to physical inactivity and depression [25,26], these often co-occurring factors may have opposing effects for individual PD risk estimates. Excessive daytime somnolence has been shown to be both a risk factor for depression as well as a frequent comorbid factor in depressed individuals, supporting their interdependency observed in the BN [27]. Diabetes received interesting edges from several nodes including SN hyperechogenicity, global cognitive deficits, sex and PD family history, and while their confidences were low, this finding might provide new hypotheses regarding biological prodromal mechanisms to be tested in future studies.…”
Section: Plos Onementioning
confidence: 72%
“…People with depression may find it difficult to fall asleep and stay asleep at night [ 30 ]. They may also have excessive daytime sleepiness or may even sleep too much [ 31 ]. At the same time, SDs can exacerbate depression, leading to a negative cycle between depression and sleep that can be difficult to break [ 28 ].…”
Section: Discussionmentioning
confidence: 99%